MODEL REHABILITASI STROKE BERBASIS MASYARAKAT DI PUSKESMAS ANTARA KOTA MAKASSAR - Idris, Wayabulani; Chairunnisa, Frida; Rasdiyanti, Andi (Jurnal Administrasi Negara, 2024)
Stroke is the leading cause of disability and death in Indonesia, with an increasing prevalence. The impact of stroke not only affects individuals, but also families and communities. In the working area of the Antara Health Center there is an increase in cases every year. This study aims to develop a model of community-based stroke rehabilitation services at the Antara Health Center in Makassar City. Qualitative research methods were used to explore important components in the development of the model and factors that improve service accessibility. The results showed that the development of the model involved the formation of a multidisciplinary team, the application of a holistic approach, the active involvement of families and communities, and the utilization of local resources. Factors that improve accessibility include proximity to services, affordable costs, community involvement, education, and government policy support. Recommendations include developing training programs, recruiting rehabilitation health workers, improving integration and communication between health facilities, developing monitoring systems, utilizing digital technology, and strengthening related policies. The implementation of this model is expected to improve the accessibility and quality of community-based stroke rehabilitation services, as well as support the recovery of patients in their own environment.